Science is not balkanized in different disciplines: being a super-specialist is not an excuse for not being a wide scientist - Marcelino Cereijido (Universidad de San Buenaventura, 2012)
As recently as three centuries ago, it was taken for granted that the Universe was a “thing” created by God, exactly as we see it. But during the XIXth century the Universe and everything it contains started to be regarded as “processes” (Cereijido, 1994a).